An Overall Glance of Evidence Supportive of One-Hour and Two-Hour Postload Plasma Glucose Levels as Predictors of Long-Term Cardiovascular Events - Mann, Baldeep K. (Int J Endocrinol, 2019)
This review summarizes the vast literature describing the long-term epidemiological studies with emphasis on postprandial glucose as a stronger predictor of cardiovascular complications as compared to fasting glucose and HbA1c. Many molecular studies also supported this fact by illustrating that postchallenge hyperglycemia is associated with elevated biomarkers of systemic inflammation in the plasma and thus increasing the chances of vascular damage. Large-scale studies have proved that vascular stiffness, brachial-ankle pulse-wave velocity, carotid intima thickness, and left ventricular hypertrophy have been associated with postprandial glucose as compared to fasting glucose or glycosylated hemoglobin.